Jezikovna uredniška politika in slovenski radijski mediji - Lengar Verovnik, Tina (Slavia Centralis, 2020)
Language Editorial Policy and the Slovenian Radio MediaIn the paper, we examine the extent to which legislation and other documents can help decision makers in shaping language editorial policy related to the medium of radio; who, in fact, are the creators and directors of language editorial policies of the (radio) media; who determines the linguistic imprint of the media – both in terms of quality and the social acceptability of expression – and how is this process undertaken. The findings were obtained through responses to targeted questions included in a survey conducted within the "Slovenian Language Policy and User Needs" target research project, and through structured interviews with editors of selected radio channels.
Keywords: language editorial policy; radio; editors; language advisers; journalists